Research and Comparative Analysis of Build Technology Programming in Java - Mayilyan, Aren K.; Hovsepyan, Levon M. (Mathematical Problems of Computer Science, 2021)
Build tools have been studied in Java environment, and a comparable analysis has been done according to the following parameters: initial learning curve, the speed of different builds, complexity, plugins, documentation and community, developer tools integrity.